Morphological and Molecular Identification of Culturable Arbuscular Mycorrhizal Fungi (AMF) Associated with Pternandra azurea from Martabe Batang Toru Forest, North Sumatra, Indonesia - Maulani, Nail Izzatul; Sukarno, Nampiah; Yulandi, Adi; Listiyowati, Sri; Kramadibrata, Kartini; Subagya, Mahmud; Anwar, Syaiful (HAYATI Journal of Biosciences, 2025)
Arbuscular Mycorrhizal Fungi (AMF) form a mutualistic symbiosis with almost all host plant species and exist in various ecosystems. Studies of AMF diversity in Sumatra tropical rainforest plants are still limited. This research aimed to isolate and identify AMF associated with Pternandra azurea from Martabe Batang Toru forest, North Sumatra. The spores were obtained from the rhizosphere of P. azurea and propagated by trap culture using Pueraria javanica, Sorghum vulgare, and Zea mays. AMF spores were isolated using wet sieving and decanting techniques, then inoculated into roots of P. javanica grown in sterile zeolite to obtain a single-species culture. The AMF were identified based on spore morphology and molecular analysis using AML1/AML2 specific primers. A total of 13 AMF single-species cultures were obtained, and based on morphological characteristics, they were identified as Claroideoglomus lamellosum, C. claroideum, Acaulospora rehmii, A. longula, and Glomus ambisporum. Further identification using molecular analysis, the cultures were identified as C. etunicatum, A. spinosa, A. longula, and G. ambisporum. Molecular identification resulted in different AMF species from morphological identification. Claroideoglomus was dominant AMF observed. All cultures formed internal hyphae, arbuscules, and vesicles within the roots. The AMF cultures obtained can be used as biofertilizers to restore degraded ecosystems.